Framing The Crisis: A Comparative Analysis On News Coverage Of Cadbury Porcine Dna Crisis In Malaysiakini And The Star Online - Jasminder, Kaur Bhullar (2021)
This research attempts to analyze and explore the news frames that were applied by The Star Online and Malaysiakini in their news articles on the Cadbury Malaysia crisis over its Halal non-compliance in the year of 2014. This is to determine if there is any difference between the two media in their reporting styles. Using media framing theory, this study therefore compares between a major mainstream newspaper and an alternative online newspaper that is known for its independent news reporting. Both The Star Online and Malaysiakini had been selected in view of its strong presence and popularity amongst the Malaysian public. The research was analyzed using both quantitative and qualitative methods to strengthen the findings by the means of content analysis. Content analysis was used to determine the frames. This analysis was carried out by using a coding book for frames adapted from Semetko and Valkenburg’s (2000) study along with two additional frames created by Wang (2014) and McKeever (2013). The results were then tested using One Way ANOVA analysis to determine if there were any significant differences in the frames used between the two news portals and textual analysis of the news articles’ headlines and paragraphs were studied to establish the slants and tone of reporting. The results from both the analysis reported there was not much significant differences in terms of frames used and the most prominent frames found were the attribution of responsibility frames and main difference was the solutions and conflict frames. However, there was a difference noted in the tone of reporting and slants used when covering the crisis where Malaysiakini had more persuasive elements in its reporting comparing with The Star that was mainly neutral.